Estudo fitoquímico e avaliação das atividades moluscicida e larvicida de tocoyena selloana k. schum (rubiaceae) - Rocha, Marcos Oliveira (2009)
Due to the system does not recognize equations and formulas the resumo and abstract can be found in the PDF file.